ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DAN DAMPAKNYA TERHADAP PENERIMAAN PAJAK, DENGAN PELAYANAN FISCUS SEBAGAI VARIABEL MODERATING - Jarno Jarno (Universitas Pamulang, 2018)
The aim of this research is to analyze and ine out the factors that influence the compliance of Individual Taxpayers and their impact on tax revenue, with fiscus service as a moderating variable. The data used are primary data with a total sample of 195 respondents.The analysis used with the Stucture Equations Model (SEM) with the LISREL 8.8 program. The test results show that knowledge of tax has a significant effect on tax compliance. Income level has a significant effect on tax compliance. Fiscus service does not significant effect on tax compliance. Tax Compliance has a significant effect novion tax revenue. Simultaneously Knowledge of taxes, income levels and fiscus services have a significant effect on tax compliance. Simultaneously tax knowledge, income level and tax compliance have a significant effect on tax revenue. iscus service can moderate between tax knowledge and tax compliance. Fiscus service can moderate between income levels and tax compliance.